Analisis Tingkat Kematangan E-Government dalam Pelayanan Surat Pengantar Nikah Melalui Ssw Alfa di Kelurahan Gayungan Kota Surabaya - Almafhira Restu Rosadi; Deby Febriyan Eprilianto (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The digital transformation of public services has encouraged the Surabaya City Government to develop the Surabaya Single Window (SSW) Alfa as a digital service platform, including for the marriage recommendation letter service at Gayungan Urban Village. Although the service has been digitalized, the maturity level of e-government implementation still requires further analysis. This study aims to analyze the e-government maturity level of the marriage recommendation letter service through the Surabaya Single Window (SSW) Alfa at Gayungan Urban Village, Surabaya City. This study employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, and were analyzed using the e-government maturity capability model developed by Valdés et al., which consists of four dimensions: E-Government Strategy, IT Governance, Process Management, and Organization and People. The results indicate that the e-government maturity level of the marriage recommendation letter service through SSW Alfa has progressed, although it has not yet reached an optimal level. In the E-Government Strategy dimension, service development is still dominated by a top-down approach, resulting in less-than-optimal public outreach. In the IT Governance dimension, system management has been implemented effectively through a clear division of responsibilities among related institutions. In the Process Management dimension, digitalization has simplified service procedures; however, a dual process of digital and manual services still exists due to the lack of integration with the SIMKAH system. In the Organization and People dimension, staff competencies and citizens’ digital literacy remain uneven.